A typology for provider payment systems in health care - Jegers, Marc; Kesteloot, Katrien; De Graeve, Diana; Gilles, Willem (Health policy (Amsterdam), 2002)
A typology to classify provider payment systems from an incentive point of view is developed. We analyse the way, how these systems can influence provider behaviour and, a fortiori, contribute to attain the general objectives of health care, i.e. quality of care, efficiency and accessibility. The first dimension of the typology indicates whether there is a link between the provider's income and his activity. In variable systems, the provider has an ability to influence his earnings, contrary to fixed systems. The second dimension indicates whether the provider's payments are related to his actual costs or not. In retrospective systems, the provider's own costs are the basis for reimbursement ex post whereas in prospective systems payments are determined ex ante without any link to the real costs of the individual provider. These different characteristics are likely to influence provider behaviour in different ways. Furthermore the most frequently used criteria to determine the provider's income are discussed: per service, per diem, per case, per patient and per period. Also a distinction is made between incentives at the level of the individual provider (micro-level) and the sponsor (macro-level). Finally, the potential interactions when several payment systems are used simultaneously are discussed. This typology is useful to classify and compare different types of payment systems as prevailing in different countries, and provides a useful framework for future research of health care payment systems.